A coupled MD-FE methodology to characterize mechanical interphases in polymeric nanocomposites. (15th August 2021) - Ries, Maximilian; Possart, Gunnar; Steinmann, Paul; Pfaller, Sebastian
Highlights: Numerical study of mechanical interphases in polymer nanocomposites. Uniaxial deformation via atomistic-continuum coupling method. Identification of material property gradients inside the interphase. Revealing elastoplastic behavior in the vicinity of filler particles. Graphical abstract: Abstract: This contribution introduces an unconventional procedure to characterize spatial profiles of elastic and inelastic properties inside polymer interphases around nanoparticles. Interphases denote those regions in the polymer matrix whose mechanical properties are influenced by the filler surfaces and thus deviate from the bulk properties. They are of particular relevance in case of nano-sized filler particles with a comparatively large surface-to-volume ratio and hence can explain the frequent observation that the overall properties of polymer nanocomposites cannot be determined by classical mixing rules, which only consider the behavior of the individual constituents. Interphase characterization for nanocomposites poses hardly solvable challenges to the experimenter and is still an unsolved problem in many cases. Instead of real experiments, we perform pseudo experiments using our recently developed Capriccio method, which is an MD-FE domain-decomposition tool specifically designed for amorphous polymers. These pseudo-experimental data then serve as input for a typical inverse parameter identification. With this procedure, spatially varying mechanical properties inside the polymer are, for the first time, translated into intuitively understandable profiles of continuum mechanical parameters. As a model material, we employ silica-enforced polystyrene, for which our procedure reveals exponential saturation profiles for Young's modulus and the yield stress inside the interphase, where the former takes about seven times the bulk value at the particle surface and the latter roughly triples. Interestingly, hardening coefficient and Poisson's ratio of the polymer remain nearly constant inside the interphase. Besides gaining insight into the constitutive influence of filler particles, these unexpected and intriguing results also offer interesting explanatory options for the failure behavior of polymer nanocomposites.